Simplification of environmental and other impact assessments – results from an international online survey. Issue 3 (4th May 2023) - Fischer, Thomas B; Fonseca, Alberto; Geißler, Gesa; Jha-Thakur, Urmila; Retief, Francois; Alberts, Reece; Jiricka-Pürrer, Alexandra
ABSTRACT: Results from an international online survey on simplification efforts in environmental assessment (EA) and other types of impact assessments (IAs) are presented. The survey, which was conducted between July and October 2022, captured responses from 45 participants who reported on developments in a total of 26 EA/IA systems. Whilst in about three quarters of these systems simplification efforts are either currently underway or planned, in particular with regards to reducing costs and time necessary for EA/IA, opposite developments were also reported on in two-thirds of the systems, including an extension of existing requirements, such as the consideration of further aspects in EA/IA and the coverage of additional actions subject to assessment. The findings are a reflection of the increasing complexities of the contexts within which EAs/IAs are applied and highlight the need for further empirical research on simplification efforts.